Gene regulation and chromatin organization: relevance of cohesin mutations to human disease. (April 2016) - Watrin, Erwan; Kaiser, Frank J; Wendt, Kerstin S
Abstract : Consistent with the diverse roles of the cohesin complex in chromosome biology, mutations in genes encoding cohesin and its regulators are found in different types of cancer and in developmental disorders such as Cornelia de Lange Syndrome. It is so far considered that the defects caused by these mutations result from altered function of cohesin in regulating gene expression during development. Chromatin conformation analyses have established the importance of cohesin for the architecture of developmental gene clusters and in vivo studies in mouse and zebrafish demonstrated how cohesin defects lead to gene misregulation and to malformations similar to the related human syndromes. Here we present our current knowledge on cohesin's involvement in gene expression, highlighting molecular and mechanistic consequences of pathogenic mutations in the Cornelia de Lange syndrome.